Tax Evasion and Corruption in the Indian Income Tax System: Causes and Remedies - Rani, Vaneeta; Arora, R. S. (Indian Journal of Finance, 2010)
Tax evasion refers to the efforts by an assessee to evade taxes by illegal means. It involves dishonest tax reporting and hiding of income. Tax evasion is a serious concern of fiscal policy all over the world. It is closely related to corruption in tax system of a country. It is unethical and shows that public does not have respect for tax system of the country. It further implies that there is something wrong with the tax system of the country. It reduces public revenue and generates black money. It has been recognized that black money is not a fund, but a stream. Thus, the amount which would have been used for economic and social development is used for anti- social activities such as gambling, speculation in real estate or stock market, financial scams, smuggling etc. Therefore, it is not only detrimental to the economic progress of the country, but is also harmful for the society at large.